Making Fahrenheit 451 "Come to Life": Sound Inquiries with Youth and Teachers. Issue 1 (21st June 2021) - Friesen, Doug; Simon, Rob
Abstract: In this article, we describe how eighth‐grade students and teacher candidates used sound and listening to remix and attune themselves (Stewart, 2011) to the dystopian novel Fahrenheit 451 by Ray Bradbury (2011). We situate our sound inquiries in relation to critical literacy (Vasquez, Janks, & Comber, 2019; Wargo, 2019) and sound education (Schafer 1992, 2005; Oliveros, 2005). The examples we share suggest how students and teacher candidates used sound to, in the words of a participating teacher candidate, make Fahrenheit 451 "come to life." This work demonstrates how sound inquiry can encourage students' transformative engagement with their surroundings, with each other, and with canonical texts like Fahrenheit 451 in critical literacy classrooms.